Functional Traits, Species Diversity and Species Composition of a Neotropical Palm Community Vary in Relation to Forest Age - Lueder, Sarah; Narasimhan, Kaushik; Olivo, Jorge; Cabrera, Domingo; Jurado, Juana G.; Greenstein, Lewis; Karubian, Jordan (Frontiers in Ecology and Evolution, 2022)
Understanding the factors that shape the diversity and composition of biotic communities in natural and human-modified landscapes remains a key issue in ecology. Here, we evaluate how functional traits, species diversity and community composition of palm trees vary in relation to biogeographic variables and forest age in northwest Ecuador. Functional traits capture essential aspects of species’ ecological tradeoffs and roles within an ecosystem, making them useful in determining the ecological consequences of environmental change, but they have not been used as commonly as more traditional metrics of species diversity and community composition. We inventoried palm communities in 950 10 x 10 m plots arrayed in linear transects placed in forests of varying age. Adult palms in forests of younger regeneration stages were characterized by species with greater maximum stem height, greater maximum stem diameter, and solitary stems. The shift in functional traits may indicate that shade tolerant palms occur preferentially in old-growth forest, or may reflect the importance of remnant canopy palms in secondary forests, or both. Moreover, younger forest age was associated with decreased abundance and altered species composition in both juvenile and adult palms, and decreased species richness in adults. These results highlight the importance of retaining intact, old-growth forest to preserve functional and species diversity and highlight the importance of considering multiple aspects of diversity in studies of vegetation communities.